Transfer of celiac disease-associated immunogenic gluten peptides in breast milk: variability in kinetics of secretion - Ruiz-Carnicer, Ángela; Segura, Verónica; Moreno, María de Lourdes; Coronel-Rodríguez, Cristóbal; Sousa, Carolina; Comino, Isabel (Frontiers in Immunology, 2024)
Background: Exposure to antigens is crucial for child immune system development, aiding disease prevention and promoting infant health. Some common food antigen proteins are found in human breast milk. However, it is unclear whether gluten antigens linked to celiac disease (CD) are transmitted through breast milk, potentially impacting the development of the infant's immune system.Objective: This study aimed to analyze the passage of gluten immunogenic peptides (GIP) into human breast milk. We evaluated the dynamics of GIP secretion after lactating mothers adopted a controlled gluten-rich diet.We prospectively enrolled 96 non-CD and 23 CD lactating mothers, assessing total proteins and casein in breast milk, and GIP levels in breast milk and urine. Subsequently, a longitudinal study was conducted in a subgroup of 12 non-CD lactating mothers who adopted a controlled gluten-rich diet. GIP levels in breast milk and urine samples were assayed by multiple sample collections over 96 hours.Results: Analysis of a single sample revealed that 24% of non-CD lactating mothers on a regular unrestricted diet tested positive for GIP in breast milk, and 90% tested positive in urine, with significantly lower concentrations in breast milk. Nevertheless, on a controlled gluten-rich diet and the collection of multiple samples, GIP were detected in 75% and 100% of non-CD participants in breast milk and urine, respectively. The transfer dynamics in breast milk samples were long-enduring and GIP secretion persisted from 0 to 72 h. In contrast, GIP secretion in urine samples was limited to the first 24 h, with inter-individual variations. In the cohort of CD mothers, 82.6% and 87% tested negative for GIP in breast milk and urine, respectively.This study definitively established the presence of GIP in breast milk, with substantial inter-individual variations in secretion dynamics. Our findings provide insights into distinct GIP kinetics observed in sequentially collected breast milk and urine samples, suggesting differential gluten metabolism patterns depending on the organ or system involved. Future research is essential to understand whether GIP functions as sensitizing or tolerogenic agents in the immune system of breastfed infants.